Comparative effectiveness of tenofovir in HIV-infected treatment-experienced patients: systematic review and meta-analysis. Issue 1 (2nd January 2017) - Ewald, Hannah; Santini-Oliveira, Marilia; Bühler, Julian-Emanuel; Vuichard, Danielle; Schandelmaier, Stefan; Stöckle, Marcel; Briel, Matthias; Bucher, Heiner C.; Hemkens, Lars G.
Abstract : Background : Antiretroviral therapy (ART) regimens for HIV infection are frequently changed. We conducted a systematic review of randomized trials (RCTs) on the benefits and harms of switching to tenofovir disoproxil fumarate (TDF)-based regimens in ART-experienced patients. Methods : We included RCTs in HIV-infected adults comparing switching to a TDF-containing regimen with maintaining or switching to another regimen. We searched MEDLINE, EMBASE, CENTRAL, LILACS, SCI, and the WHO Global Health Library. We assessed bias with the Cochrane tool and synthesized data using random-effects meta-analyses and Peto's approach. For further analyses, we added data from a previous systematic review in treatment-naïve patients. Results : 17 RCTs with 2210 patients were included. All but one study had a high risk of bias. There was no significant association of switching to TDF-based regimens with mortality, fractures, CD4-cell count, body fat, virological failure, LDL-, and HDL-cholesterol. TDF-based regimens decreased total cholesterol (mean difference −12.05 mg/dL; 95% CI −20.76 to −3.34), trigylcerides (−14.33 mg/dL; −23.73 to −4.93), and bone mineral density (BMD; hip: −2.46%; −3.9 to −1.03; lumbar spine −1.52%; −2.69 to −0.34). Effects on estimated glomerular filtration (eGFR) were inconsistent and depended on the measurement. Adding 22 RCTs from 8297 treatment-naïve patients gave consistent results with then significant reductions of LDL (−7.57 mg/dL; −10.37 to −4.78), HDL (−2.38 mg/dL; −3.83 to −0.93), and eGFR (−3.49 ml/min; −5.56 to −1.43). Conclusions : Switching to TDF-based regimens is associated with reductions of BMD and lipid levels and possibly lowered kidney function. The evidence is limited by the high risk of bias.